A transparent scratch-resistant PC material
By using surface modifiers such as polyester silicone and bioacid esters in PC materials, combined with other additives, the problem of insufficient scratch resistance and mechanical properties of the surface of PC materials is solved, and high transparency and excellent scratch resistance are achieved.
Patent Information
- Application Number
- CN202411981042.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Due to the high degree of freedom of molecular chains and low surface hardness, existing PC materials are prone to scratches and wear, and poor compatibility when blended with PMMA, resulting in reduced transparency and reduced mechanical properties, which cannot meet application scenarios in different fields.
Polyester silicone and bioacid esters are used as surface modifiers, combined with chain extenders, antioxidants, UV stabilizers and tougheners, and through specific proportional combinations, the surface scratch resistance and mechanical properties of PC materials are improved.
It significantly improves the scratch resistance and mechanical properties of the surface of PC materials, avoids pearlescent fog phenomenon when blended with PMMA, and meets the application needs of different fields.
Smart Images

Figure CN119775749A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a transparent scratch-resistant PC material. Background Art
[0002] Polycarbonate (PC) is a widely used engineering plastic with excellent strength and elastic coefficient, high heat resistance, high dimensional stability and high transparency. The transmittance of PC at a thickness of 1mm can reach more than 90%. This feature allows it to replace inorganic glass materials and be used in the fields of automobiles, electronic appliances and optical components. However, due to the high degree of freedom of the molecular chain of PC materials, there is a large space between molecules, and the low surface hardness, it is easy to produce scratches and wear on the surface of the material. These defects greatly limit the application of PC in some fields.
[0003] In order to improve the scratch resistance of PC surface, the existing technology is to blend PC and polymethyl methacrylate (PMMA) for extrusion. However, due to the poor compatibility of PC and PMMA, the alloy is often mixed unevenly, which not only reduces the transparency of PC / PMMA alloy, but also produces alloy pearlescence. In addition, the poor mechanical properties of PMMA will cause the mechanical properties of PC / PMMA alloy to drop sharply, which will also greatly limit the use of the product.
[0004] Patent CN 201410328787.4 discloses a transparent, scratch-resistant PC / PMMA alloy material and a preparation method. The PC phase and the PMMA phase can be well dispersed and blended to be compatible, and the resulting PC / PMMA alloy material has high transparency and scratch resistance. However, this method is difficult to operate, and does not take into account the tensile strength, flexural modulus, notched impact strength, and weather resistance of the PC material, and cannot meet the application scenarios in different fields.
[0005] Therefore, it is of great significance to study a transparent scratch-resistant PC material to solve the problems existing in the prior art. Summary of the invention
[0006] The purpose of the present invention is to solve the problems existing in the prior art and provide a transparent scratch-resistant PC material.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A transparent scratch-resistant PC material comprises the following components in parts by weight:
[0009]
[0010] The surface modifiers are polyester siloxanes and bio-based acid esters.
[0011] As the preferred technical solution:
[0012] The transparent scratch-resistant PC material as described above, wherein the PC resin is bisphenol A type.
[0013] For the transparent scratch-resistant PC material as described above, under the test conditions of 300° C. and 1.2 kg, the melt index of the PC resin is 1 to 10 g / 10 min.
[0014] In the transparent scratch-resistant PC material as described above, the mass ratio of polyester siloxane to bio-based acid ester is 1:2-3.
[0015] The transparent scratch-resistant PC material as described above, wherein the chain extender is BASF chain extender 4468.
[0016] In the transparent scratch-resistant PC material as described above, the antioxidant is one or more of a hindered phenol antioxidant and a phosphite antioxidant.
[0017] In the transparent scratch-resistant PC material as described above, the UV stabilizer is one or more of a benzotriazole UV stabilizer, a benzodiphenone UV stabilizer and a triazine UV stabilizer.
[0018] In the transparent scratch-resistant PC material as described above, the toughening agent is acrylate, random terpolymer or methyl methacrylate and silicone core-shell structure.
[0019] Invention mechanism:
[0020] The present invention uses two surface modifiers, bio-based acid ester and polyester siloxane, and a chain extender in combination. First, the introduction of the chain extender will increase the cross-linking viscosity of the PC material, and the PC can react better with the surface modifier, so that the scratch resistance of the PC material surface is significantly improved; at the same time, the bio-based acid ester is a low molecular weight microcrystalline compound and will not affect the transparency of the PC material. In addition, when the present invention uses polyester siloxane (polyester siloxane has no effect on the transparency of the PC material) and bio-based acid ester as two surface modifiers in a specific ratio, it is found that the scratch resistance effect is better than that of using bio-based acid ester alone. This is because both contain ester groups, which can promote each other to react with the PC material to improve the scratch resistance of the PC material surface; and the addition of polyester siloxane reduces the addition amount of bio-based acid ester. Due to the reduction in the addition amount of the bio-based acid ester surface modifier and the effect of the flexible chain segment of the polyester siloxane surface modifier, the impact strength of the material is significantly improved. In addition, the present invention finds that as the melt index of PC decreases, the scratch resistance of the material surface is continuously improved. This is because the lower the melt index of the material, the greater the viscosity, and the more complete the reaction between PC and the surface modifier during screw extrusion. In addition, in order to ensure that the material can be used outdoors and in high-toughness scenarios, antioxidants, UV stabilizers and toughening agents can also be added to further improve the weather resistance and impact toughness of the material.
[0021] Beneficial effects:
[0022] (1) Compared with PC / PMMA alloy, the transparent scratch-resistant PC material of the present invention can effectively avoid the problem of pearlescent fogging caused by poor compatibility between PC and PMMA materials.
[0023] (2) A transparent scratch-resistant PC material of the present invention uses antioxidants, polyester siloxane, bio-based acid esters, chain extenders, toughening agents and other additives in combination, which can improve the surface scratch resistance of the material on the one hand, and on the other hand, it is better than the commercially available samples ( KH3310UR), the mechanical properties of the scratch-resistant PC material of the present invention have been qualitatively improved. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0025] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0026] (1) Tensile strength: Refer to ISO527 and test the tensile strength (MPa) of scratch-resistant PC at 50 mm / min.
[0027] (2) Flexural strength and flexural modulus: Referring to ISO178, the flexural strength (MPa) and flexural modulus (MPa) of scratch-resistant PC were tested under the test condition of 1.3 mm / min.
[0028] (3) Notched impact strength: Refer to ISO179 and test the notched impact strength of scratch-resistant PC at 23°C and 2J (KJ / m 2 ).
[0029] (4) Density: Refer to ISO1183 and test the density of scratch-resistant PC at 23°C (g / cm 3 ).
[0030] (5) Pencil hardness: Refer to ASTM D3363 and test the pencil hardness @1Kgf of scratch-resistant PC at room temperature (25°C).
[0031] (6) Transmittance: Refer to ASTM D1003 to test the transmittance of scratch-resistant PC at 1 mm (%).
[0032] The sources of some of the substances in the present invention are as follows, and similar substances are distinguished by different numbers:
[0033] Bisphenol A type PC resin 1: polycarbonate with a melt index of 35 g / 10 min under the test conditions of 300° C. and 1.2 kg.
[0034] Bisphenol A type PC resin 2: polycarbonate with a melt index of 15 g / 10 min under the test conditions of 300° C. and 1.2 kg.
[0035] Bisphenol A type PC resin 3: polycarbonate with a melt index of 3 g / 10 min under the test conditions of 300° C. and 1.2 kg.
[0036] Surface modifier 1: polyester siloxane, Chengdu SILMER 5150.
[0037] Surface modifier 2: bio-based acid ester, Shanghai Shengdian New Materials Co., Ltd. SD199.
[0038] Chain extender: BASF chain extender 4468.
[0039] Antioxidant 1: Hindered phenol antioxidant, BASF antioxidant 1076.
[0040] Antioxidant 2: Phosphite antioxidant, BASF antioxidant 168.
[0041] UV stabilizer: benzotriazole UV stabilizer, BASF UV-P light stabilizer.
[0042] Toughener: Random terpolymer, SK Global Chemical Co., Ltd. EMA AX8900.
[0043] PMMA: Under the test conditions of 230°C and 3.8 kg, the melt index is 21 g / 10 min.
[0044] Example 1
[0045] A transparent scratch-resistant PC material comprises the following components in parts by weight:
[0046]
[0047] The transparent scratch-resistant PC material has a tensile strength of 66.9MPa, a flexural strength of 88.4MPa, a flexural modulus of 2680MPa, and a notched impact strength of 20.5KJ / m 2 , density is 1.19g / cm 3 The transmittance is 88.6%, the pencil hardness is 2H, and it is visually transparent and has no pearlescent effect.
[0048] Comparative Example 1
[0049] A PC material is basically the same as Example 1, except that the surface modifier and the BASF chain extender 4468 are replaced by the same weight proportion of bisphenol A type PC resin 3, that is, the surface modifier and the BASF chain extender 4468 are omitted.
[0050] The density of PC material is 1.19g / cm 3 The transmittance is 90.1%, the pencil hardness is 2B, and it is visually transparent and has no pearlescent effect.
[0051] By comparing Comparative Example 1 with Example 1, it can be found that the scratch resistance of the surface of the modified PC material in Example 1 is greatly improved. This is because the reaction between the surface modifier and PC increases the surface hardness of the material, making the surface of the material have higher scratch resistance.
[0052] Comparative Example 2
[0053] A PC material is basically the same as Example 1, except that the surface modifier and BASF chain extender 4468 are replaced by the same weight portion of bisphenol A type PC resin 3, and the same weight portion of bisphenol A type PC resin 3 is replaced by 30 parts of PMMA.
[0054] The tensile strength of PC material is 58MPa, the flexural strength is 60.5MPa, the flexural modulus is 2420MPa, and the notched impact strength is 5.5KJ / m 2, density is 1.18g / cm 3 The transmittance is 58.6%, the pencil hardness is 2H, and it is visually pearly and foggy.
[0055] Comparing Comparative Example 2 with Example 1, it can be seen that under the same pencil hardness, the notched impact strength and flexural modulus of Example 1 are higher than those of Comparative Example 2, and the material is transparent and has no pearlescent phenomenon. This is because the silicon content of the surface modifier 1 of Example 1 is low and the surface modifier 2 is a low molecular weight microcrystalline compound, neither of which affects the material transmittance. However, the compatibility of PMMA and PC in Comparative Example 2 is poor, resulting in phase separation, thereby reducing the transmittance, generating pearlescent fogging, and causing a serious decrease in mechanical properties.
[0056] Comparative Example 3
[0057] A PC material is basically the same as Example 1, except that the total amount of surface modifier 1 and surface modifier 2 added remains unchanged, and the ratio between the two is changed from 1:2 to 1:1.
[0058] The tensile strength of PC material is 67.4MPa, the flexural strength is 89.6MPa, the flexural modulus is 2590MPa, and the notched impact strength is 22.3KJ / m 2 , density is 1.19g / cm 3 The transmittance is 86.9%, the pencil hardness is 1H, and it is transparent without pearlescent luster when visually inspected.
[0059] Comparative Example 4
[0060] A PC material is basically the same as Example 1, except that the total amount of surface modifier 1 and surface modifier 2 added remains unchanged, and the ratio of the two is changed from 1:2 to 2:1.
[0061] The tensile strength of PC material is 60.1MPa, the flexural strength is 76.5MPa, the flexural modulus is 2520MPa, and the notched impact strength is 24.4KJ / m 2 , density is 1.19g / cm 3 The transmittance is 86.9%, the pencil hardness is 1H, and it is transparent without pearlescent luster when visually inspected.
[0062] By comparing Comparative Examples 3 to 4 with Example 1, it can be found that when the surface modifier addition ratio is 1:2, the pencil hardness of the PC material is the highest, reaching 2H. Therefore, when surface modifier 1 and surface modifier 2 are added in a ratio of 1:2, the comprehensive performance of the material is optimal.
[0063] Comparative Example 5
[0064] A PC material is based on Example 1, except that the surface modifier 1 is replaced by the surface modifier 2 in the same weight fraction, that is, the surface modifier 1 is omitted.
[0065] The notched impact strength of the transparent scratch-resistant PC material is 10.8KJ / m 2 , density is 1.19g / cm 3 The transmittance is 89.4%, the pencil hardness is 1H, and it is visually transparent and has no pearlescent effect.
[0066] By comparing Comparative Example 5 with Example 1, it can be found that when surface modifier 1 and surface modifier 2 are used in combination, the performance is better than that of surface modifier 2 alone. For example, the notched impact strength is increased from 10.8 KJ / m 2 Increased to 20.5KJ / m 2 , the pencil hardness is increased from 1H to 2H, an order of magnitude higher; this is because both surface modifiers contain ester groups, which can promote the reaction between them during the screw extrusion process to improve the surface hardness of the material. On the one hand, the introduction of surface modifier 1 reduces the amount of surface modifier 2 added; on the other hand, the flexible segments in the polyester siloxane surface modifier can better absorb and disperse energy when the material is impacted, thereby improving the impact resistance of the material. The effects of these two aspects greatly improve the notched impact strength of the material.
[0067] Comparative Example 6
[0068] A PC material is basically the same as that in Example 1, except that the bisphenol A type PC resin 3 is replaced by the bisphenol A type PC resin 1 in the same weight fraction.
[0069] The notched impact strength of PC material is 17.9KJ / m 2 , density is 1.19g / cm 3 The transmittance is 89.3%, the pencil hardness is HB, and it is transparent without pearlescent luster when visually inspected.
[0070] Comparative Example 7
[0071] A PC material is basically the same as that in Example 2, except that the bisphenol A type PC resin 3 is replaced by the bisphenol A type PC resin 2 in the same weight fraction.
[0072] The notched impact strength of PC material is 18.6KJ / m 2 , density is 1.19g / cm 3 The transmittance is 89.1%, the pencil hardness is 1H, and it is transparent without pearlescent luster when visually observed.
[0073] By comparing Comparative Examples 6 to 7 with Example 1, it can be found that the lower the melt index of the PC material, the better the effect of the surface modifier. This is because the lower the melt index of the material, the more complete the reaction between the surface modifier and PC during the screw extrusion process, making the scratch resistance of the PC material better.
[0074] Comparative Example 8
[0075] A PC material, basic embodiment 1, differs only in that the Bass chain extender 4468 is replaced by the same weight fraction of bisphenol A type PC resin 3.
[0076] The notched impact strength of PC material is 19.4KJ / m 2 , density is 1.19g / cm 3 The transmittance is 89.5%, the pencil hardness is 1H, and it is transparent without pearlescent luster when visually inspected.
[0077] By comparing Comparative Example 8 with Example 1, it can be found that adding a chain extender can increase the pencil hardness of the PC material from 1H to 2H. This is because the chain extender 4468 can cross-link the molecular chains of the PC material and thus increase the viscosity of the system. The reaction between the PC material and the surface modifier is more complete, thereby further improving the scratch resistance of the PC surface.
[0078] Example 2
[0079] A transparent scratch-resistant PC material comprises the following components in parts by weight:
[0080] Bisphenol A type PC resin 3 94.4 parts;
[0081]
[0082] The transparent scratch-resistant PC material has a tensile strength of 68.5MPa, a flexural strength of 91.4MPa, a flexural modulus of 2820MPa, and a notched impact strength of 17.1KJ / m 2 , density is 1.19g / cm 3 The transmittance is 89.1%, the pencil hardness is 3H, and it is visually transparent and has no pearlescent effect.
[0083] Comparing Example 2 with Example 1, it can be found that when the amount of chain extender 4468 added is 2 parts, the pencil hardness of the material is increased from 2H to 3H.
[0084] Example 3
[0085] A transparent scratch-resistant PC material comprises the following components in parts by weight:
[0086]
[0087] The transparent scratch-resistant PC material has a tensile strength of 66.2MPa, a flexural strength of 84.2MPa, a flexural modulus of 2620MPa, and a notched impact strength of 24.8KJ / m 2 , density is 1.19g / cm 3 The transmittance is 88.6%, the pencil hardness is 2H, and it is visually transparent and has no pearlescent effect.
[0088] Example 3 Compared with Example 2 and Example 1, when the chain extender 4468 is increased to 2 parts and 1.5 parts of toughening agent is added, the notched impact strength is improved, from 17.1 KJ / m 2 and 20.5KJ / m 2 Increased to 24.8KJ / m 2 , and the pencil hardness remains at 2H level.
[0089] Example 4
[0090] A transparent scratch-resistant PC material comprises the following components in parts by weight:
[0091] Bisphenol A type PC resin 3 91.9 parts;
[0092]
[0093] The transparent scratch-resistant PC material has a tensile strength of 64.8MPa, a flexural strength of 82.5MPa, a flexural modulus of 2520MPa, and a notched impact strength of 29.6KJ / m 2 , density is 1.19g / cm 3 The transmittance is 88.6%, the pencil hardness is 2H, and it is visually transparent and has no pearlescent effect.
[0094] Comparing Example 4 with Example 3, it can be found that when the toughening agent content is increased to 2.5 parts, the notched impact strength of the PC material is further improved to 29.6 KJ / m 2 , and the pencil hardness remains at 2H level, allowing the material to be used in scratch-resistant and high-toughness products.
Claims
1. A transparent scratch-resistant PC material, characterized in that The composition comprises the following components in parts by weight: The surface modifiers are polyester siloxanes and bio-based acid esters.
2. A transparent scratch-resistant PC material according to claim 1, characterized in that: PC resin is bisphenol A type.
3. A transparent scratch-resistant PC material according to claim 2, characterized in that: Under the test conditions of 300°C and 1.2kg, the melt index of PC resin is 1-10g / 10min.
4. A transparent scratch-resistant PC material according to claim 1, characterized in that: The mass ratio of polyester siloxane to bio-based acid ester is 1:2-3.
5. The transparent scratch-resistant PC material according to claim 1, characterized in that: The chain extender is BASF chain extender 4468.
6. The transparent scratch-resistant PC material according to claim 1, characterized in that: The antioxidant is one or more of a hindered phenol antioxidant and a phosphite antioxidant.
7. The transparent scratch-resistant PC material according to claim 1, characterized in that: The UV stabilizer is one or more of a benzotriazole-based UV stabilizer, a benzodiphenone-based UV stabilizer, and a triazine-based UV stabilizer.
8. The transparent scratch-resistant PC material according to claim 1, characterized in that: The toughening agent is acrylate, random terpolymer or methyl methacrylate and silicone core-shell structure.
Citation Information
Patent Citations
A transparent, scratch-resistant PC / PMMA alloy material and its preparation method
CN104086969B